PERBANDINGAN KINERJA ALGORITMA BIC, CUBIC DAN HTCP PADA TOPOLOGI DUMBBELL DAN SIMPLE NETWORK MENGGUNAKAN NS2 - Rian Fahrizal; Wahyu Dewanto; Sujoko Sumaryono (Jurusan Teknik Informatika, 2012)
High speed computer networks with a large waiting time is a common from of network in the future. In this network are commonly used TCP algorithms have difficullty in sending data. There are several algorithms that has used the BIC, CUBIC and HTCP. These algorithms needs to be tested to determine its performance when apllied to the network topology with two dumbbells, and simple network. Teh results obtained testing the algorithms is best HTCP performance by having the smallest value.